2021
DOI: 10.1038/s41598-021-98530-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of collimator angles in dual-arc volumetric modulated arc therapy planning for whole-brain radiotherapy with hippocampus and inner ear sparing

Abstract: To optimize the collimator angles in dual-arc volumetric modulated arc therapy (VMAT) plans for whole-brain radiotherapy with hippocampus and inner ear sparing (HIS-WBRT). Two sets of dual-arc VMAT plans were generated for 13 small-cell lung cancer patients: (1) The collimator angles of arcs 1 and 2 (θ1/θ2) were 350°/10°, 350°/30°, 350°/45°, 350°/60°, and 350°/80°, i.e., the intersection angle of θ1 and θ2 (Δθ) increased. (2) θ1/θ2 were 280°/10°, 300°/30°, 315°/45°, 330°/60°, and 350°/80°, i.e., Δθ = 90°. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Within the study's parameters, the selected CRA angles did not signi cantly affect the conformity and homogeneity of radiation distribution to the target volume, as supported by non-signi cant differences (p > 0.05) in Table 2. This contrasts with Sun et al's VMAT study, where signi cant dosimetric improvements, including in the CI and HI, were observed as the collimator intersection angle (Δθ) approached 90°, emphasizing the need for precise CRA optimization in VMAT [11].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Within the study's parameters, the selected CRA angles did not signi cantly affect the conformity and homogeneity of radiation distribution to the target volume, as supported by non-signi cant differences (p > 0.05) in Table 2. This contrasts with Sun et al's VMAT study, where signi cant dosimetric improvements, including in the CI and HI, were observed as the collimator intersection angle (Δθ) approached 90°, emphasizing the need for precise CRA optimization in VMAT [11].…”
Section: Discussionmentioning
confidence: 57%
“…Multiple studies have investigated the impact of Collimator Rotation Angle (CRA) on optimal dose distribution in VMAT treatment plans [7][8][9][10][11][12]. Variations in dose delivery due to differences in CRA angles have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collimator angles for counterclockwise and clockwise arcs were 10° and 350°, respectively, to reduce the tongue and groove effect and the effect of interleaf leakage. 21 The anisotropic analytical algorithm (AAA) was used for the dose calculation with heterogeneous correction and a grid resolution of 2 mm. Figure 1c shows the dose distribution in the VMAT-10MV plan for the phantom with a 5 mm bolus.…”
Section: Methodsmentioning
confidence: 99%
“…For advanced radiation therapy techniques such as VMAT and RapidArc (Varian Medical System, a treatment planning and delivery method derived from VMAT) with higher delivery efficiency 1 , the radiation field in each control point is divided into multiple sub-fields with varying aperture sizes due to the movement of muti-leaf collimator leafs. During dose delivery, these sub-fields are changed over time to adjust the intensity distribution of the field 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%